Etika Hidup Orang Jawa Menurut Serat Kandha Bumi Karya Ki Padmasusastra (Sebuah Kajian Sosiologi sastra) - Hidayati, Dyah Ayu Ikaning; Werdiningsih, Yuli Kurniati; Sulanjari, Bambang (Universitas PGRI Semarang, 2021)
This study aimed to describe the form of Javanese ethics of life in Ki Padmasusastra's Serat Kandha Bumi. Life ethics contains an attitude of life in which there is an attitude of harmony and respect. The life ethics referred to are all Javanese orientations to achieve goals in life as well as in interacting with other humans. Meanwhile, the Javanese referred to are figures in Serat Kandha Bumi whose orientation in life and in their daily lives cannot be separated from elements of Javanese ethics. The method used to reveal the Javanese ethics of life in Serat Kondha Bumi is qualitative. The resulting data is in the form of words; phrase; sentence; and paragraph. The data were obtained from text descriptions in Serat Kondha Bumi which explain the attitudes of Javanese in the form of dialogue, monologue and narration. The theory used is literary sociology with a focus on the ethics of Javanese life. The results of this study are Javanese life ethics in religion which includes pracaya and mituhu attitudes, Javanese life ethics with oneself includes a rila (real) attitude and sabar (patience), and Javanese life ethics in social life including ethok-ethok (dissimulating), wedi (eeriness), and sungkan (hesitate).